2021
DOI: 10.1108/bfj-07-2021-0721
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the quality characteristics of kefir fortified with olive (Olea europaea) leaf extract

Abstract: PurposeThis study aims to produce a new type of healthy functional kefir by adding olive (Olea europaea) leaf extract and to determine its potential effect on the quality (physicochemical, sensory, phenolic contents and antioxidant properties) of kefir samples during storage at 4°C for 21 days.Design/methodology/approachFor this purpose, four kefir samples were produced by using olive leaf extract in different amounts (A: 0% (control), B: 0.1%, C: 0.15% and D: 0.35%). The physicochemical, sensory, phenolic con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…An increase in AA was also observed in the whey remaining after acid coagulation, which was significantly higher compared to enzymatic coagulation (p < 0.0001), correlating with the results of the TP (Figure 3). Although the influence of OLE on the AA of cheese has not been studied in detail, some previous studies have also shown that the addition of OLE leads to an increase in the antioxidant activity of yogurt [8,19] and kefir [54]-dairy products that are also produced by acid coagulation.…”
Section: Antioxidant Activity (Aa)mentioning
confidence: 99%
“…An increase in AA was also observed in the whey remaining after acid coagulation, which was significantly higher compared to enzymatic coagulation (p < 0.0001), correlating with the results of the TP (Figure 3). Although the influence of OLE on the AA of cheese has not been studied in detail, some previous studies have also shown that the addition of OLE leads to an increase in the antioxidant activity of yogurt [8,19] and kefir [54]-dairy products that are also produced by acid coagulation.…”
Section: Antioxidant Activity (Aa)mentioning
confidence: 99%
“…Rutin is effective against P. aeruginosa bacteria, Candida albicans , and Candida neoformans . Several studies have revealed that the phenolic components of olive leaf extract, particularly oleuropein and hydroxytyrosol, have powerful antioxidant and anticancer properties [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%